Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1128/msystems.01194-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Mycobacterium avium Complex Reveals Signatures of Environment-Specific Adaptation and Community Acquisition

Abstract: Members of the Mycobacterium avium complex (MAC), a group of mycobacteria encompassing M. avium and its closest relatives, are omnipresent in natural environments and emerging pathogens of humans and animals. MAC infections are difficult to treat, sometimes fatal, and increasingly common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…In particular, isolates from humans and animals differed. Similarly, this has also been demonstrated in isolates from human patients and their environment [ 39 ]. In the United States, in central North Carolina, a higher incidence of pulmonary mycobacteriosis was found to be influenced by housing in hydric and acidic soils [ 40 ].…”
Section: Searching For Patients’ Predisposition To Infection and Sour...mentioning
confidence: 53%
“…In particular, isolates from humans and animals differed. Similarly, this has also been demonstrated in isolates from human patients and their environment [ 39 ]. In the United States, in central North Carolina, a higher incidence of pulmonary mycobacteriosis was found to be influenced by housing in hydric and acidic soils [ 40 ].…”
Section: Searching For Patients’ Predisposition To Infection and Sour...mentioning
confidence: 53%
“…The genetic variability of isolated strains in different regions of the world cannot be excluded either. Although different species and subspecies in the MAC complex do not have identical MIC 50 and MIC 90 values [ 94 ], the five lineages of M. avium may also differ in the level of intrinsic resistance to antibacterial drugs [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genome of MAC was relatively large, consisting of approximately 5.8 Mbp. Studies of the MAC genome has identified numerous genes and pathways involved in virulence and drug resistance as well as variation in gene content and organization among different strains, which could contribute to differences in virulence and drug resistance [55,56]. Understanding the functions of these virulence factors is crucial for the development of effective therapies against mycobacterial infections.…”
Section: Plos Onementioning
confidence: 99%